Affectation and Rainfall Contribution of Tropical Cyclones in Puerto Rico from 1980 to 2016 - José C. Fernández-Alvarez; Rogert Sorí; Albenis Pérez-Alarcón; Raquel Nieto; Luis Gimeno (The 3rd International Electronic Conference on Atmospheric Sciences, 2020)
This study investigated the number of tropical cyclones (TCs) that affected Puerto Rico during the June-November hurricane season in the period 1980–2016, and their contribution to the total precipitation. Special attention was dedicated to assessing the role of atmospheric-oceanic teleconnections in the formation of TCs that affect this island. The HURDAT2 tropical cyclone climatology database and the multi-source weighted set precipitation (MSWEPv2) data with a spatial resolution of 0.1° × 0.1° were used. A total of 92 TCs within a 500-km radius of Puerto Rico were identified for the study period. Contrary to what was expected, a similar percentage of affectation was found between those TCs formed under El Niño and La Niña conditions. Regarding the North Atlantic Oscillation, a 23.91 % of the 92 TCs that affected Puerto Rico formed under the negative phase, while the 13.04% during the positive phase, which is explained in agreement with previous findings with the weakening and shift to the south and west of the Azores High during the negative phase of North Atlantic Oscillation. The role of the Sea Surface Temperature on the genesis of TCs that affected Puerto Rico was also assessed through the Atlantic Meridional Mode and the Atlantic Warm Pool area. It is confirmed that the affectation of TCs in Puerto Rico is highly related to the eastward extension of the Atlantic Warm Pool and the Sea Surface Temperature gradient in the tropical North Atlantic region. Indeed, a northward shift in latitude and longitude in genesis position was found from July to November. Finally, a monthly analysis revealed that in August and September the maximum mean rain contribution from TC was ~17% for the grid but with values in the 20–30% interval.